1950
DOI: 10.1084/jem.91.5.505
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Hypersensitivity in the Rabbit

Abstract: Recently, the histologic and serologic responses in the rabbit to single, large intravenous injections of purified bovine serum proteins have been described (1). These responses were: (1) To bovine serum gamma globulin--The development in most animals of a transient intracapillary glomerulonephritis, together with focal lesions of the liver, heart, and joints, the acute phase occurring from 1 to 2 weeks following injection; (2) to crystallized bovine serum albumin--The development in only about half of the rab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
7
0

Year Published

1951
1951
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 104 publications
(8 citation statements)
references
References 28 publications
1
7
0
Order By: Relevance
“…The anaphylactic activity of complement was initially postulated over 100 years ago [72], and subsequent studies in passive cutaneous anaphylaxis directly demonstrated a role for complement but did not implicate the complement anaphylatoxins as we know them today [73,74,75]. In the late sixties, multiple groups independently documented the isolation and functional activity of C3a and C5a using purified complement proteins [76,77,78].…”
Section: Discussionmentioning
confidence: 99%
“…The anaphylactic activity of complement was initially postulated over 100 years ago [72], and subsequent studies in passive cutaneous anaphylaxis directly demonstrated a role for complement but did not implicate the complement anaphylatoxins as we know them today [73,74,75]. In the late sixties, multiple groups independently documented the isolation and functional activity of C3a and C5a using purified complement proteins [76,77,78].…”
Section: Discussionmentioning
confidence: 99%
“…It was known that when immune complexes are circulating during the phase of immune elimination of infused heterologous scrum proteins total C' activity is decreased [6,33,39]. It was found that when the total C' titer decreased, titers of each of the classical hemolytic C' components also decreased, and heat-stable anti-C' activity appeared in the serum ( fig.…”
Section: Experimental Manipulation Of the Complement Profilementioning
confidence: 99%
“…These experiments were based on the known anti-C' or C'-fixing activities of immune complexes, aggregated human y-globulin (AHGG), zymosan and endotoxic lipopolysaccharides (LPS) in vivo and in vitro [3,4,6,20,32,33,39]. These agents also affected the C' profile in two distinct patterns [2, 12, 16 a, 32].…”
Section: Experimental Manipulation Of the Complement Profilementioning
confidence: 99%
“…In several types of experimental nephritis in animals, the presence of such complexes in the glomeruli and their role in the production of glomerular inflammation has been well documented (9)(10)(11)(12)(13). In humans, hypocomplementemic nephritides in which glomerular immune complexes are demonstrable are those accompanying serum sickness, prolonged sepsis, and systemic lupus erythematosus, as well as the nephritis which follows a streptococcal infection (4, 1-16).…”
mentioning
confidence: 99%